FROM FORESIGHT-RESEARCH TO FORESIGHT-ORGANIZATIONS - N. Sh. Yepifanova (Russian Journal of Economics and Law)
The modern trends in foresight-research are analyzed, the necessity to carry out such research at enterprises is grounded. The role of innovations, knowledge and learning in foresight-organizations formation is defined. The stage and necessary elements of foresight-organizations are determined, their interconnection is.